A mining strategy for Latin America and the Caribbean (Washington, D.C. World Bank, 1996)
"Technical papers that assess the current state of mining in parts of Latin America, and propose a framework for growth in the mineral sector. Specific coverage for four country groups: Mexico/Venezuela, Chile, Bolivia/Peru, and Argentina/Ecuador/Pana ma"--Handbook of Latin American Studies, v. 57.
Keywords: Mineral industries -- Environmental aspects -- Caribbean Area; Mineral industries -- Environmental aspects -- Latin America; Mineral industries -- Government policy -- Caribbean Area; Mineral industries -- Government policy -- Latin America; Sustainable development -- Caribbean Area; Sustainable development -- Latin America